Effect of Vitamine E and C Supplementation on Meat Characteristics of Coloured Broiler Birds in Summer Season - Pati, P.K.; Mohapatra, A.K.; Patra , T. (Journal of Meat Science, 2011)
Two hundred forty day-old coloured broiler chicks were divided in to four dietary treatment groups, viz. T1 - control group was fed with basal diet; T2 - basal diet plus vitamin E @ 500 mg/kg of feed; T3-basal diet plus vitamin C @ 250 mg/kg of feed; T4- basal diet plus vitamin E & C @ 500mg/kg and @ 250 mg/kg of feed. The experiment was continued up to 8 weeks of age in summer season. The chicks were fed with starter ration up to 21 days and finisher ration from 22 to 56 days of age. The dressing percentage for T1, T2, T3 and T4 was 75.93, 75.35, 74.88 and 78.07, respectively. The water holding capacity of the meat for the control and three treatment groups were 25.97, 25.92, 26.15 and 26.29 %, respectively. The meat pH value of control and treatment groups was from 6.44 to 6.48. The thio-barbituric acid (TBA) value of T1, T2, T3 and T4 was 0.280, 0.226, 0.240 and 0.210 (mg of malonaldehyde/kg), respectively. The flavour, juiciness, texture and overall acceptability of cooked chicken nuggets kept under refrigerated storage from 0 to 14th day showed a non-significant decreasing trend.